Uncovering the Hurdles and Devising Strategies for the Integration of Intercultural Components in EFL Curricula in Sub-Saharan Africa - ZOUNHIN TOBOULA, Coffi Martinien; KOTTIN, Assogba Evariste; TCHAGNONHOU, Dèkandé Sylvestre (My University, 2024)
This study investigates the challenges and strategies for integrating intercultural components in English language curricula in the francophone Sub-Saharan African countries of Benin and Togo. The study population consisted of 135 EFL teachers, curriculum developers, and 117 EFL learners representing diverse linguistic and cultural backgrounds in these countries. Data were collected and analyzed using a mixed-methods approach, combining qualitative interviews and quantitative surveys. The study found that 70% of participants recognized the importance of intercultural competence in English language education. However, 60% of educators encountered limited resources as a significant hurdle in integrating intercultural components into the curriculum. Effective strategies were devised, including incorporating authentic cultural materials (endorsed by 80% of participants) and implementing student-centered and interactive pedagogies (supported by 75% of participants) to overcome these challenges. Additionally, 65% of educators emphasized the need for professional development opportunities to enhance intercultural teaching skills. The statistical analysis of the collected data indicated a strong correlation (r = 0.76, p < 0.001) between the integration of intercultural components and improved intercultural competence among students. Furthermore, after implementing intercultural components in their English language curricula, most educators (89%) reported a positive impact on students’ language proficiency and cultural awareness. Recommendations stemming from this study include the allocation of additional resources for curriculum development (supported by 80% of participants), improvements in teacher training programmes (recommended by 70% of participants), and the promotion of cross-cultural understanding within the education system (endorsed by 85% of participants). By addressing the identified challenges, it is anticipated that integrating intercultural components will enhance intercultural competence and effective communication skills among English language learners in Benin and Togo.
Keywords: Intercultural components; EFL curricula; Education stakeholders; Curriculum development; intercultural competence